Unmasking communication challenges with personal protective equipment amid the COVID-19 apocalypse - Yadav, Anita; Baghel, Jyoti; Prakash, Avinash; Rawat, Rajneesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
The ongoing COVID-19 pandemic has dramatically changed our lives and health care system too. According to World Health Organisation (WHO), there have been 164,523,894 confirmed cases of COVID-19 including 3,412,032 deaths in the world (20 May 2021). This unprecedented public health emergency has affected both patients and clinicians experience regarding traditional face-to-face consultations. Amongst the most pressing of these challenges is the requirement to wear mandated personal protective equipment (PPE) which includes gloves, gowns, shoe covers, head covers, masks, respirators, eye protection, face shields, and goggles. These protective gear helps in preventing the transmission of the COVID-19 virus to both health professionals and the patients.